2015
DOI: 10.4000/cybergeo.26730
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel comparison of large urban systems

Abstract: For the first time the systems of cities in seven countries or regions among the largest in the world (China, India, Brazil, Europe, the Former Soviet Union (FSU), the United States and South Africa) are made comparable through the building of spatio-temporal standardised statistical databases. We first explain the concept of a generic evolutionary urban unit ("city") and its necessary adaptations to the information provided by each national statistical system. Second, the hierarchical structure and the urban … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 14 publications
2
41
0
4
Order By: Relevance
“…The first part of this concluding chapter is a selection of salient points from our evolutionary theory of urban systems that are discussed in several of the chapters. As many of our results were already published (Pumain et al 2015;Cura et al 2017;Pumain & Reuillon 2017) 2 it was possible to confirm them, or to bring more different evidence or contradictory views. For each of these lively research questions, we report the convergent opinions that emerged from the topics discussed, as well as the open and even controversial perspectives for future work.…”
supporting
confidence: 51%
“…The first part of this concluding chapter is a selection of salient points from our evolutionary theory of urban systems that are discussed in several of the chapters. As many of our results were already published (Pumain et al 2015;Cura et al 2017;Pumain & Reuillon 2017) 2 it was possible to confirm them, or to bring more different evidence or contradictory views. For each of these lively research questions, we report the convergent opinions that emerged from the topics discussed, as well as the open and even controversial perspectives for future work.…”
supporting
confidence: 51%
“…In a previous paper using about the same data sets, we have compared the shape of the urban hierarchical organization in each country or world region and classified the trajectories of cities with respect to the evolution of their population (Pumain et al ). In the present article, we concentrate on Zipf's and Gibrat's models and investigate further the related statistical evidence about the urban growth process and its connection with urban hierarchies.…”
mentioning
confidence: 99%
“…Several studies have demonstrated that specific historical events in urban systems are required to understand the size, distribution and infrastructure development, which affect the "universal change" from rural isolated areas to diversified, concentrated and hierarchized urban settlements. [11][12][13]. A similar explanation is provided in Allen [11] referring to the rank size rule by [14] about the interaction of urban settlements where explanation of growth is economic competition and another is the appearance of industrial satellites and wealthy housing buildings attracting population.…”
Section: Cities and Regions As Complex Self-organizing Systemsmentioning
confidence: 81%